Peningkatan Keterampilan Proses Sains Siswa Melalui Discovery Learning Pada Materi Tekanan Zat Cair: Indonesia - Wulan Indri Safitri; Dilla Oktaviana; Yuspira Luci Febriyanti ; Auralia Putri ; Susilawati (UNIB Press, 2026)
This study aims to examine the effectiveness of the Discovery Learning model in improving students’ science process skills and learning outcomes on the topic of liquid pressure. This study employed a Classroom Action Research (CAR) design conducted in two cycles, consisting of planning, action, observation, and reflection stages. The participants were 20 ninth-grade students of SMP Al-Faruqi. Data were collected through observation and tests and analyzed using descriptive quantitative techniques. The results indicate a significant improvement in students’ learning outcomes, with the average score increasing from 70.05 in the pretest to 82.05 in the posttest. In addition, learning mastery improved from 35% to 90%. Students’ science process skills also showed improvement, particularly in questioning and reasoning, reflecting greater engagement in scientific inquiry. These findings demonstrate that Discovery Learning effectively enhances both conceptual understanding and science process skills through active and experiential learning. Therefore, Discovery Learning can be considered an effective approach to science instruction that improves students’ learning outcomes and scientific skills.